Cryptosporidium oocysts: are they still a risk for human population? A case study in Italy. (30th September 2020) - Pignata, C; Bonetta, S i; Bonetta, S a; Cacciò, S M; Sannella, A R; Gilli, G; Carraro, E
Abstract: Over the past decade, several outbreaks of cryptosporidiosis have been reported in many EU countries in association with the consumption of contaminated drinking water, recreational waters, food consumption and contact with animals. The aim of this study was to evaluate the occurrence of Cryptosporidium oocysts in a drinking water treatment plant (DWTP) located in a rural area of northern Italy. Influent and effluent samples at the DWTP, together with tap water samples from a public fountain were collected for three years (2013-2016). All samples were analysed for the presence of Cryptosporidium spp. oocysts by the EPA Method 1623 based on immunomagnetic separation (IMS)/immunofluorescence assay (IFA), complemented by 4, 6-diamidino-2-phenylindole (DAPI) staining. The detection has been implemented with a reverse transcriptase-PCR (RT-PCR) protocol to evaluate the oocyst viability. The results highlighted a high variability of oocyst concentrations in all samples (mean 4.3 - 5.8/100 L) and a high percentage variability of the DAPI-positive specimens (mean 48.2% - 40.3%). Conversely, RT-PCR did not reveal the presence of any viable C. parvum and C. hominis oocysts. A nested PCR targeting Cryptosporidium 18S ribosomal DNA was carried out in two water samples to deepen the understanding of the obtained results. This test revealed the presence of a particular Cryptosporidium genotype associated with wild animals in the river and in tap water. Although the recovered Cryptosporidium genotype is not a human pathogen, its presence demonstrates the existence of a potential pathogen Cryptosporidium spp. contamination risk. Moreover, these results underline the importance of considering unconventional (not bacterial) biological contaminations (protozoa) in water resources in rural areas, including those of developed countries. Key messages: The supply source and the drinking water treatment plant examined represent a classic example of a system that requires continuous monitoring to guarantee population health. Cryptosporidium oocysts may still be a Public Health problem even in industrialized countries, especially in rural and mountain areas.